Can we eat to treat—and even beat—hypertension?. (2nd June 2022) - Webster, Brian
Abstract : While hypertension is classed as a long-term condition—implying that it is incurable—it can be prevented, managed and even reversed through lifestyle changes, argues Brian Webster.